Pranas Dovydaitis as a Critic of M. Guyau’s Theory of Morals - Balčius, Jonas (Problemos, 1976)
In the present paper the author seeks to elucidate the formation of P. Dovydaitis’s views on morals. Pranas Dovydaitis, a clerical ideologist and philosopher Neo-Thomist who lived in bourgeois Lithuania, while still a student at Moscow University in 1910, in his first scientific work “Criticism of M. Guyau’s Morals” on the basis of the works of the French positivist tried to define his own attitude to morals and especially to its origin. In his opinion the attempt of the French positivist to give a scientifically substantiated methodology to the origin of morals, deriving it from expediency allegedly inherent in animate nature, is unacceptable. P. Dovydaitis concludes that the solution of the problem of the genesis of morals is possible only on the basis of Thomistic methodology.